Cultural approaches in state border governance of the Republic of Indonesia–Democratic Republic of Timor Leste in Napan village - Seran, Remigius; Nino, Handrianus; Mbiri, Adeodata Laniria Charla Barros (Journal of Law Science, 2024)
Study This focuses on approach cultural in managing the governance of Indonesia's borders with Republic Democratic Timor Leste which focuses on the Napan Village point. Approach study Qualitative with method studies cultural. Dissected research results with human security and is based on several study previous, prove that exists mobilization between society to strengthen House customs and rites existing customs maintained, for the sake of strengthening institutionalization strengthening traditions exists system justice custom through track diplomacy between second public existing customs in existence of different countries. That matter possible Because exists connection the strong and strong kinship and brotherhood status that is framed in connection blood, and rites custom between second split party.